Correction: A Well-Defined Readily Releasable Pool with Fixed Capacity for Storing Vesicles at Calyx of Held. - Kashif Mahfooz; Mahendra Singh; Robert Renden; John F Wesseling (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1004855.].